Implante percutáneo o mínimamente invasivo de prótesis valvular aórtico (TAVI): Una solución creciente para el tratamiento de la estenosis aórtica de pacientes inoperables y de alto riesgo para cirugía de reemplazo valvular aórtico (RVAO) - Dussaillant N., Gastón (Revista Hospital Clínico Universidad de Chile, 2015)
Aortic stenosis, the most common form of cardiac valve disease in the elderly, has an ominous prognosis, when the degree of stenosis is severe and symptoms develop. Symptoms and survival prognosis can be dramatically improved with open cardiac surgery and valvereplacement. However in the presence of severe comorbidities and advanced age the risk of the operation can be extremely high in terms of mortality and postoperative morbidity. In the last decade the development of Transcatheter Aortic Valve Implantation (TAVI) has permitted the effective and safe treatment of these patients in a less invasive procedure involving the insertion and implantation of a valve prosthesis on a beating heart. In this article we describe the procedure characteristics, the selection process of candidates and discuss the results obtained with this technique.